2015
DOI: 10.18410/jebmh/2015/418
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Co - Morbidity in Persons With Hansen’s Disease

Abstract: To estimate prevalence of psychiatric co-morbidity and its effect on quality of life in persons with Hansen's disease. METHOD: The study was conducted on around 80 persons above 18 year age with Hansen's disease in outpatient department dermatology and in leprosy home. Participants were diagnosed cases of Hansen's disease, selected randomly and were evaluated with socio demographic questionnaire, Duke's general health questionnaire, DSM-5 self rated level 1 cross cutting symptom measure-adult and WHO-QOL-BREF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…which This was in agreement with the study by Bhatia, et al [12] , .Against what had beenand inconsistent with reported in some other previous studies [13][14][15] that reported reporting depression was the most common psychiatric diagnosis followed by anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…which This was in agreement with the study by Bhatia, et al [12] , .Against what had beenand inconsistent with reported in some other previous studies [13][14][15] that reported reporting depression was the most common psychiatric diagnosis followed by anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Investigators also described other conditions linked to leprosy including sleep disorder, dementia, hysteria, epilepsy, paranoid and psychotic state, senile degeneration, delusional disorder, hypochondriacal disorder, adjustment disorders, substance-related disorders, somatic symptom disorder, somatoform disorders, hyperactivity disorder and premenstrual dysphoric disorder. (Miyeko, 1962; Kumar and Verghese, 1980; Nishida et al ., 2006; Su et al ., 2012; Rocha-Leite et al ., 2014; Nagargoje et al ., 2015; Mahendra et al ., 2016). Hypochondriacal disorder and dementia were the only conditions that were mentioned in more than one study.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that gender also influences mental wellbeing. According to Joseph and Rao (1999) and Nagargoje et al (2015), female leprosy-affected persons in India had a significantly higher prevalence of psychiatric co-morbidity and a lower quality of life, in all domains, in comparison with male patients.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations